The Association between external training load, perceived exertion and total quality recovery in Sub-Elite youth football - Teixeira, José Eduardo (2022)
Moderate to very large correlation between internal training load, external training load, and recovery status have been reported in elite youth football. However, little is known about subelite youth football training environments. Objective: The purpose of this study was to assess the association between training load and recovery status in young subelite football players. Methods: Twenty under-15, twenty under-17, and twenty under-19 players were monitored over a 6-week period during the first month of the 2019-2020 competitive season. The global positioning system technology (GPS) was used to collect external training load variables. The internal training load variables were monitored using the rating of perceived exertion (RPE) scale and session RPE (sRPE). The recovery status was assessed by the total quality recovery (TQR). A total of 18 training sessions and 324 observation cases were collected. Results: Small to moderate correlation between internal and external load was observed r( = -0.316 to 0.136, p < 0.05). Correlations between recovery status and external load were moderate for U15 (r = -0.326 to -0.240, p < 0.05), U17 (r = -0.316 to 0.136, p < 0.05) and U19 (r = -0.301 to 0.282, p < 0.05). The association between perceived exertion and external training load is only significant for U19 subelite football players. Conclusion: Current research suggested that subelite youth football players were more likely to have lower capacity to judge training exertion. Additionally, recovery status was positively correlated with acceleration and deceleration movements. This study provides a new overview about training load and recovery in subelite youth training environment. Future researche should examine the between- and within-individual nonlinearity across training load and recovery variations.